Children and Drug Safety Balancing Risk and Protection in Twentieth-Century America - Connolly, Cynthia A (Rutgers University Press, 2018)
Winner of the 2018 Arthur J. Viseltear Award from the Medical Care Section of the American Public Health Association​ Children and Drug Safety traces the development, use, and marketing of drugs for children in the twentieth century, a history that sits at the interface of the state, business, health care providers, parents, and children. This book illuminates the historical dimension of a clinical and policy issue with great contemporary significance-many of the drugs administered to children today have never been tested for safety and efficacy in the pediatric population. Each chapter of Children and Drug Safety engages with major turning points in pediatric drug development; themes of children's risk, rights, protection and the evolving context of childhood; child-rearing; and family life in ways freighted with nuances of race, class, and gender. Cynthia A. Connolly charts the numerous attempts by Congress, the Food and Drug Administration, the American Academy of Pediatrics, and leading pediatric pharmacologists, scientists, clinicians, and parents to address a situation that all found untenable. Open access edition funded by the National Endowment for the Humanities. The text of this book is licensed under a Creative Commons Attribution NonCommercial-NoDerivatives 4.0 International License: https://creativecommons.org/licenses/by-nc-nd/4.0/